Caries and ABO Secretor Status in a Hungarian Population of Children and Adolescents: An Exploratory Study - Kárpáti, K.; Braunitzer, G.; Toldi, J.; Turzó, K.; Virág, K.; Reiche, W.T.; Rakonczay, Z.; Nagy, K. (Caries research, 2014)
ABO blood group antigen (ABGA) secretion into the saliva and other body fluids is a well-known phenomenon, and there is evidence to suggest a link between secretor status and the appearance of caries. It has been proposed that secretion of these antigens into the saliva might be caries-preventive, however, this proposition is still a matter of debate. Our aim was to examine the relationship between caries experience and secretor status in a group of Hungarian children and adolescents in a cross-sectional study. Altogether 130 children and adolescents participated in the study (aged 6-18 years). Participants were divided into two groups according to dentition (i.e. mixed and permanent). ABGA were determined from saliva. The DMF-T and dmf-t (decayed, missing, and filled) indices were calculated, as well as the oral health hygiene index-simplified plaque index. Association of these indices with secretor status was examined. In mixed dentition, the mean dmf-t values were significantly lower in the secretor group (2.1 ± 0.52 SEM), as compared to the nonsecretor group (3.8 ± 0.93 SEM; p < 0.05, Mann-Whitney U test). The finding that children of mixed dentition are apparently better protected against caries suggests that the assumed protective effect might be associated with deciduous teeth, but given the general paucity of knowledge about this topic, further research is indicated.